Faktor-Faktor yang Mempengaruhi Struktur Modal Perusahaan Transportation Seirices Go Public di Bursa Efek Indonesia - Sri Mulyati; Muriir Halim Rosyadi (Jurnal Aplikasi Bisnis, 2017)
Thisstudy aimed to determine the effect ofvariables, consisting of Return on Assets (ROA), firm size, sales growth and the structure of the asset (asset structure) on the capital structure. Companies used in this study are Transportation Services companies, listed in Indonesia Stock Exchange for the period of2008-2010. Samples that meet the criteria to be investigated consist of 14 companies. An analytical technique used in this study is multiple regressions and hypothesis testing conducted partially and simultaneously. The analysis shows that simultaneously. Return on Assets (ROA), firm size, sales growth, and the structure of the asset (asset structure) significantly influence the company's capital structure. Partially, the firm size, and sales growth have a significantly positive effect on the capital structure while Return on Assets (ROA) and the structilre of the asset (asset structure) do not significantly affect company'scapital structure.